“Bonnie und Kleid”: Female Terrorists and the Hysterical Feminine - Clare Bielby (University of Edinburgh, 2006)
This paper will explore the ways in which the feminine, in particular the hysterical feminine, is invoked in media representations of violent women in order to contain the threat they pose. I shall draw on a number of mainstream German newspapers, both leftwing, liberal “quality” journals, such as Der Spiegel and, to a lesser extent, Stern, and more reactionary papers, such as Bild and Die Welt. It is my contention that although these journals may seem to be of different quality, the same paradigms are being mobilized with regard to the violent female terrorist: paradigms that are firmly anchored in the German popular imagination of the 1970s.